The sphinx in the city : urban life, the control of disorder, and women - Wilson, Elizabeth (University of California Press, 1992)
"Elizabeth Wilson's elegant, provocative, and scholarly study uses fiction, essays, film, and art, as well as history and sociology, to look at some of the world's greatest cities-London, Paris, Moscow, New York, Chicago, Lusaka, and Sao Paulo-and presents a powerful critique of utopian planning, anti-urbanism, postmodernism, and traditional architecture. For women the city offers freedom, including sexual freedom, but also new dangers. Planners and reformers have repeatedly attempted to regulate women-and the working class and ethnic minorities-by means of grandiose, utopian plans, nearly destroying the richness of urban culture. City centers have become uninhabited business districts, the countryside suburbanized. There is danger without pleasure, consumerism without choice, safety without stimulation. What is needed is a new understanding of city life and Wilson gives us an intriguing introduction to what this might be."